Electronic resource librarianship a practical guide for librarians - Talbott, Holly, 1987- (Practical guides for librarians ;, 2018)
"Electronic Resource Librarianship is a guide that will steer librarians through the intricacies of the daily e-resource grind while giving them the tools to handle even the most complex challenges. The book discusses project planning in an environment of continuous change, as well as advice on passing newly acquired e-resource knowledge to others"--